Cardiovascular Effects of Androgen Deprivation Therapy in Prostate Cancer: Contemporary Meta-Analyses. Issue 3 (March 2020) - Hu, Jiun-Ruey; Duncan, Meredith S.; Morgans, Alicia K.; Brown, Jonathan D.; Meijers, Wouter C.; Freiberg, Matthew S.; Salem, Joe-Elie; Beckman, Joshua A.; Moslehi, Javid J.
Abstract : Androgen deprivation therapy is a cornerstone of prostate cancer treatment. Pharmacological androgen deprivation includes gonadotropin-releasing hormone agonism and antagonism, androgen receptor inhibition, and CYP17 (cytochrome P450 17A1) inhibition. Studies in the past decade have raised concerns about the potential for androgen deprivation therapy to increase the risk of adverse cardiovascular events such as myocardial infarction, stroke, and cardiovascular mortality, possibly by exacerbating cardiovascular risk factors. In this review, we summarize existing data on the cardiovascular effects of androgen deprivation therapy. Among the therapies, abiraterone stands out for increasing risk of cardiac events in meta-analyses of both randomized controlled trials and observational studies. We find a divergence between observational studies, which show consistent positive associations between androgen deprivation therapy use and cardiovascular disease, and randomized controlled trials, which do not show these associations reproducibly. Abstract : Supplemental Digital Content is available in the text.